O processo de construção da consciência da negritude pelo homem negro na vida urbana - Sellmer, Ygor Santini (2025)
This dissertation investigates the process of constructing Blackness among middleclass Black men in São Paulo, considering the impact of daily experiences within a context marked by structural racism. Grounded in the author’s personal experience, the research adopts a qualitative approach, conducting reflective interviews with seven Black men aged 20 to 39 residing in the city. Data were analyzed using thematic analysis techniques based on Jungian Psychology, exploring both conscious and unconscious individual dimensions as well as cultural complexes. The findings suggest that familial, educational, and social experiences significantly influence the construction of racial identity, revealing feelings of exclusion, discrimination, and belonging. Additionally, the process of Blackness is gradual, unfolding through development and involving the overcoming of cultural and personal complexes. The study highlights the importance of self-esteem and the appreciation of cultural roots as essential factors for individuation. This research contributes to the field of Clinical Psychology by emphasizing the need for therapeutic practices that address the specificities of racial experiences